1999
DOI: 10.1111/j.1600-0536.1999.tb06054.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the European standard series for patch testing in children A 3‐year single‐centre study of 337 patients

Abstract: Results of patch tests in 337 children aged 1 to 15 performed in our paediatric unit during the past 3 years have been analysed retrospectively in order to optimize the patch test series and to assess their relevance. This study represents the most important single-centre study reported so far over a short period. We found a positive patch test rate of 66%, with a peak incidence among children less than 3 years of age (88% versus 58.9%). The most common allergens were metals, especially nickel, fragrances and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
98
1
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 11 publications
9
98
1
6
Order By: Relevance
“…More than 9 out of 10 infants with moderate AD tested before 1 year of age react positively and in isolation to the atopy patch test, the earliest atopy marker, with a subsequent decrease with age (19). It is striking to note that the incidence of contact allergy in children with atopic dermatitis follows a similar pattern (20). Furthermore, the recently identified ''Lucky Luke'' dermatitis (21) due to rubber components of disposable diapers, which seems currently to be the commonest form of contact dermatitis before 2 years of age, is also seen nearly exclusively in children with AD, who usually are spared of AD lesions in this protected location.…”
Section: Hypothesismentioning
confidence: 82%
“…More than 9 out of 10 infants with moderate AD tested before 1 year of age react positively and in isolation to the atopy patch test, the earliest atopy marker, with a subsequent decrease with age (19). It is striking to note that the incidence of contact allergy in children with atopic dermatitis follows a similar pattern (20). Furthermore, the recently identified ''Lucky Luke'' dermatitis (21) due to rubber components of disposable diapers, which seems currently to be the commonest form of contact dermatitis before 2 years of age, is also seen nearly exclusively in children with AD, who usually are spared of AD lesions in this protected location.…”
Section: Hypothesismentioning
confidence: 82%
“…In contrast to our study, Clayton et al 3 in the United Kingdom reported that 33% of children had positive reactions to nickel, although only 3 cases were deemed of current relevance. Nickel was the most common allergen with positive reactions in the study by Roul et al, 8 but positive reactions did not often correlate with exposure. In contrast to nickel, patch tests with positive reactions for thimerosal (15.4%) are more often of little to no current or past relevance in our population.…”
Section: Commentmentioning
confidence: 99%
“…The allergen hit list outlined by Wöhrl et al, 6 the allergens with a positive yield outlined by Beattie et al, 2 the most frequent allergens in children identified by Clayton et al, 3 and a shortened standard series for children outlined by Roul et al 8 provide similar guidance for screening allergens with the highest yield for patch testing children in particular locales.…”
Section: Commentmentioning
confidence: 99%
“…In addition, many atopic children develop erythema and desquamation on plantar surfaces of both feet during spring or in relation to sports. This may lead to the misdiagnosis of shoes' contact allergy where potassium dichromate, rubber additive, p-pheny-lenediamine (PPD), and PTBF resin were described as the most common sensitizers [32]. Exposure to 'black henna' tattoos and to hair dyes are the main cause of strong patch test reactions to PPD in children aged 14 years and younger [33].…”
Section: Clinical Pictures and Patch Testing In Ad Childrenmentioning
confidence: 99%
“…Roul et al [32] also suggest reducing the number of tests: in children up to 6 years old, a series of 17 allergens; and in older, a baseline series of 29 to 31 allergens, depending on the testing center. Recently, Jacob et al have suggested the use of at least the basic 20-allergen from North American pediatric series, in the routine screening of children ages 6-12 years [45].…”
Section: Clinical Pictures and Patch Testing In Ad Childrenmentioning
confidence: 99%